Role of Personal Savings in Financial Tech Impact on Family Planning in Indonesia - Cahyono, Dwi; Susbiyani, Arik; Lestari, Evi; Fauziyah, Fauziyah; Qomariah, Nurul; Guntur, Yohanes Sri (Aptisi Transactions On Technopreneurship (ATT), 2025)
The study explored the impact of financial technology (FinTech) on family financial planning (FFP) among young families in Indonesia, with a focus on Personal Saving Orientation (PSO) as a moderating variable. Financial technology has significantly transformed personal financial management, enabling better access to tools for budgeting, tracking, and saving. However, its direct impact on FFP remains underexplored, especially in developing countries like Indonesia.This research aims to analyze the role of FinTech in shaping financial behaviors and examine PSO moderating influence on the relationship between FinTech adoption and FFP. The study employed a quantitative approach using Structural Equation Modeling (SEM) to analyze data collected from 217 young families. The variables examined include PSO, FinTech adoption, and FFP. The findings reveal that FinTech positively impacts PSO (estimate = 0.799, p-value = 0.000), highlighting its role in improving financial habits and saving behaviors. While the direct relationship between FinTech and FFP is not significant (p-value > 0.05), PSO effectively enhances FinTech influence on FFP, emphasizing its critical role as a moderating factor. This study underscores the importance of integrating PSO into financial strategies to optimize the benefits of FinTech, particularly for young families. These findings provide practical insights for FinTech developers to design tools that promote saving behaviors and for policymakers to encourage financial literacy and inclusion. By aligning with Sustainable Development Goals (SDGs), this research contributes to poverty reduction, economic stability, and financial well-being.